A longitudinal investigation of the reliability of memories for trauma and other emotional experiences - Peace, Kristine; Porter, Stephen (My University, 2004)
This study examined the relative consistency and characteristics of memories for trauma and other non-traumatic emotional experiences over time. A community sample of 52 participants who reported a recent traumatic event were asked to recall both the traumatic and a positive emotional experience in two interviews separated by approximately three months (M = 105.39 days). The recollections were elicited with either a free narrative, cognitive interview, guided imagery, or written narrative approach. Results indicated that traumatic experiences were recalled more reliably over time than other emotional experiences. Traumatic memory imagery tended to persist in memory (with no apparent impairment), whereas features of positive memories were subject to considerable distortion, regardless of interview style. The findings contribute to the understanding of the impact of trauma on memory with the passage of time.
Keywords: memory; trama; emotions; recollection